The Role of Work Motivation and Work Environment in Improving Job Satisfaction - Basalamah, Muhammad Syafii A.; As’ad, Ajmal (Manunggal Halim Jaya, 2021)
This study aims is to analyze the effect of work motivation on the satisfaction of management lecturers and analyze the effect of the work environment on the satisfaction of management lecturers at a private university in the city of Makassar. This type of research is explanatory research. The sample of this research is management lecturers at private universities in Makassar city, Data use purposive random sampling total 105 respondent. The research period was carried out in February 2020-May 2020. The method of analysis in this study was multiple regression analysis. The results of this study indicate that motivation has a significant effect on job satisfaction. This study proves that both theoretically and previous empirical studies explain that increasing work motivation will increase the job satisfaction of lecturers at private universities in the city of Makassar. According to empirical studies, motivation from a financial perspective can encourage someone to do work. This factor has a more significant influence than the influence of motivation on lecturer job satisfaction. The universities and study programs must improve indicators in the work environment to create comfortable working conditions so that it will increase the job satisfaction of private university lecturers in the city of Makassar.